Current Role of Urethrolysis and Partial Excision in Patients Seeking Revision of Anti-incontinence Sling. Issue 3 (March 2020) - Drain, Alice; Enemchukwu, Ekene; Shah, Nihar; Syan, Raveen; Rosenblum, Nirit; Nitti, Victor W.; Brucker, Benjamin M.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2019;25:409–414) Stress urinary incontinence (SUI) affects 5% to 30% of women. After the introduction of the first synthetic midurethral sling (transvaginal tape) in1996, there was a rapid rise in the number of midurethral slings available, and these products were widely adopted and used.